Analysis of the wing mechanism movement parameters of selected beetle species (Coleoptera) - Geisler, Tomasz; Topczewska, Sandra (Zielona Góra: Uniwersytet Zielonogórski)
This study presents a structural and functional analysis of the wing bending and folding mechanism of a selected beetle species. Insect motility studies, with regard to the anatomical structure, were performed. The main inner wing structures were highlighted and their mechanical properties and functions were determined. The structure parameters as mechanisms bodies that allow wings of various beetle species to bend and fold were defined.
Keywords: bionic; wing; movement parameters; folding